EARLY DETECTION AND STIMULATION INTERVENTIONS FOR CHILDREN WITH SPEECH DELAY: A CASE STUDY IN EARLY CHILDHOOD EDUCATION - Sri Aulia (UNMUHBABEL Press, 2026)
This study aims to describe the condition of speech delay in children aged 4-5 years at RA Ar Rahmaan Jakarta and analyze the causal factors and treatment efforts through early childhood development detection programs. A descriptive qualitative method with a case study approach was employed involving two children identified with speech delay among 42 students. Data were collected via observation, interviews, and documentation, then analyzed using the Miles and Huberman model. Findings reveal that speech delay is caused by insufficient language stimulation, excessive gadget use, and unresponsive parenting, which significantly hinders verbal interaction. While subjects initially relied on sign language and possessed limited vocabulary, they showed significant progress following consistent and measurable language stimulation within the detection program. This occurs because a lack of two-way interactive environments prevents children's speech functions from being optimally sharpened during their sensitive developmental periods. In conclusion, early detection and effective collaboration between teachers and parents are proven effective in mitigating language barriers. These results provide an essential reference for designing appropriate intervention strategies for language development disorders in school settings.